2012
DOI: 10.1111/j.1443-1661.2012.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric glomus tumor: Analysis of endosonographic characteristics and computed tomographic findings

Abstract: Among submucosal tumors (SMT), gastric glomus tumors are rare vascular tumors, and only a few cases where glomus tumors have been differentiated from other mesenchymal tumors by endoscopic ultrasonography (EUS) or computed tomography (CT) have been reported. In this case series, we aimed to analyze the EUS and CT characteristics of gastric glomus tumors. Seven patients with gastric glomus tumors were retrospectively enrolled in this study. EUS showed that all the tumors were located in the fourth EUS layer (mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
0
20
0
3
Order By: Relevance
“…Following the administration of contrast medium, these tumors demonstrate strong enhancement on arterial-phase scans and persistent enhancement on portal venous-phase scans (2). By contrast, the density of gastrointestinal stromal tumors is lower and these do not exhibit prolonged enhancement in the delayed phase (9). EUS features of gastric glomus tumors are heterogeneous, hypoechoic or hyperechoic, and hypervascular masses with internal hyperechoic spots and few tubular structures, mostly located on the fourth echolayer (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the administration of contrast medium, these tumors demonstrate strong enhancement on arterial-phase scans and persistent enhancement on portal venous-phase scans (2). By contrast, the density of gastrointestinal stromal tumors is lower and these do not exhibit prolonged enhancement in the delayed phase (9). EUS features of gastric glomus tumors are heterogeneous, hypoechoic or hyperechoic, and hypervascular masses with internal hyperechoic spots and few tubular structures, mostly located on the fourth echolayer (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize surgical trauma and the inflammatory response, the benign nature and small median size [varying between 2 and 3 cm (19)] of glomus tumors allows them to be removed by laparoscopic wedge resection (9,2022), or endoscopic submucosal enucleation in select cases (22,23) where the lesion is not close to the pylorus, porta hepatis and along the lesser curvature (24). …”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies may be diagnostically helpful; on endoscopic ultrasound, the tumor has distinct borders and shows a characteristic peripheral halo sign. 3 On dynamic contrast-enhanced computer tomography, these tumors may show hemangioma-like globular enhancement. In one study, this pattern was exclusively observed in gastric or duodenal glomus tumors and was absent in other subepithelial lesions such as gastrointestinal stromal tumor (GIST), schwannoma, ectopic pancreas, and leiomyoma.…”
Section: Glomus Tumorsmentioning
confidence: 99%
“…Is endoscopic ultrasonography (EUS) an independent competent in such a task [11][12][13][14][15][16][17][18][19]? Moreover, some SMTs can only be surgically excised.…”
Section: Introductionmentioning
confidence: 99%